Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2012
DOI: 10.1145/2207676.2208676
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing web use on smartphones

Abstract: The current paper establishes empirical patterns associated with mobile internet use on smartphones and explores user differences in these behaviors. We apply a naturalistic and longitudinal logs-based approach to collect real usage data from 24 iPhone users in the wild. These data are used to describe smartphone usage and analyze revisitation patterns of web browsers, native applications, and physical locations where phones are used. Among our findings are that web page revisitation through browsers occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(56 citation statements)
references
References 29 publications
1
54
0
1
Order By: Relevance
“…It means that the participants are confused to respond to the content display emotionally. The different polarization supports the Tossell"s statement that the way of the users to access various websites depends on the technology and platform used [23].…”
Section: International Journal Of Socialmentioning
confidence: 56%
See 1 more Smart Citation
“…It means that the participants are confused to respond to the content display emotionally. The different polarization supports the Tossell"s statement that the way of the users to access various websites depends on the technology and platform used [23].…”
Section: International Journal Of Socialmentioning
confidence: 56%
“…In addition, emotional response could also construct a customer or user e-satisfaction when accessing online website [22]. While accesing online website, the user could be identified based on technology device (personal computer, laptop, tablet or smartphone) and web browser platform (mobile and non-mobile web browser) [23]. Therefore, this study explores the importance of measuring emotional response in various technology devices and platform used to access online news websites.…”
Section: Introductionmentioning
confidence: 99%
“…In [52] the authors demonstrated from a two month smartphone usage study that all users have unique device usage patterns. Many other works [3,[53][54][55][56][57][58][59] utilize data gathered from groups of real smartphone users to emphasize this same conclusion. The conclusions of these studies are in line with those of our user studies that we performed as part of this work, as well as in our prior work [37].…”
Section: Related Workmentioning
confidence: 84%
“…The empirical patterns associated with the mobile internet usage were identified in Tossell, Kortum, Rahmati, Shepard, and Zhong (2012). There were 24 participants of 19.2 years average age in this study.…”
Section: Related Workmentioning
confidence: 99%